O kierunkach rozwoju kontroli administracji: [on tendencies of development of control of administration] (Studia Prawnicze / The Legal Studies, 1981)
Beginning with February l980 and binding from September of this year the law on Chief Administrative Court is counted among legal acts composing Polish legal system. It caused a real revolution in Polish system of control of administration although full meaning of changes recently made could be fairly determined only in next few years when the practice of this court stabilizes. We can say, however, that by introducing the system of judicial control of administration in Poland we have filled up a gap which existed in our legal system, the distance which separated us from other systems.Administrative courts have many advantages but also several weaknesses which are distinctly mentioned in legal science. Adjudication of cases takes considerable time and is connected with costs and troubles, evidenciary proceed- ings are laborious and troublesome. These are the reasons why all over the world now development of simple, direct forms of control of administration such as e.g. ombudsman in Scandinavia can be observed. There was a chance to introduce a similar form of control in Poland as well when Committees of Social Control had been set up. However, adopted model of such committees turns them into organs of programming, organizing and controlling character rather and their ties with society are insignificant.In social life besides individual decisions, administrative decisions in general matters play fundamental role, e.g. decisions concerning inhibitants of towns, districts, blocs, etc. There is a great number of such decisions especially in the field of economy. In present system the citizens have practically no decisive way to express their dissent with such decisions. What is more, in recent legal acts, e.g. in law on environmental protection or product quality, adopted concept is such that the burdons rest on administration and enterprises while social elements are totally eliminated from decision making in such matters. This solu- tion should be submitted to critical evaluation.Now state administration is in many cases not only a “manager” but also a “host” in individual cases. Reglamentation of deficit goods and services is a common phenomenon. Decisions made in such matters are generally discretional. Thus, we should do our best to organize the system of control over such decisions in a right and efficient way. The situation - such as a present one - in which they are out of control is inacceptable. It is necessary to work out procedures and institutions by means of which the citizens would be able to execute their rights in this domain.